Small diameter vascular graft with fibroblast cells and electrospun poly (L-lactide-co-epsilon-caprolactone) scaffolds: Cell Matrix Engineering - Jang, Bong Seok; Cheon, Ja Young; Kim, Soo Hyun; Park, Won Ho (TAYLOR & FRANCIS LTD, 2018)
Electrospun scaffolds have been widely used in tissue engineering due to their similar structure to native extracellular matrices (ECM). However, one of the obstacles limiting the application of electrospun scaffolds for tissue engineering is the nano-sized pores, which inhibit cell infiltration into the scaffolds. To overcome this limitation, we approached to make layers which are consisted of cells onto the electrospun sheet and then tubular structure was constructed by rolling. We called this as Cell Matrix Engineering' because the electrospun sheets were combined with the cells to form one matrix. They maintained 3-D tubular structures well and their diameters were 4.1mm (+/- 0.1mm). We compared the mechanical and biological properties of various vascular grafts with the electrospun PLCL sheets of different thickness. In these experiments, the vascular graft made with thin sheets showed a better cell proliferation and attachment than the grafts made with thick sheets because the thin layer allowed for more efficient mass transfer and better permeability than the thick layer. Culturing under physiological pulsatile flow condition was demonstrated in this work. These dynamic conditions provided the improved mass transport and aerobic cell metabolism. Therefore, the Cell Matrix Engineered vascular graft holds a great promise for clinical applications by overcoming the limitations associated with conventional scaffolds.